2022
DOI: 10.3390/jcm11030596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Positive Airway Pressure on Lipid Profiles in Obstructive Sleep Apnea: A Meta-Analysis

Abstract: Background: Obstructive sleep apnea (OSA) is associated with dyslipidemia. However, the effects of continuous positive airway pressure (CPAP) treatment on lipid profiles are unclear. Methods: PubMed/Medline, Embase and Cochrane were searched up to July 2021. Randomized controlled trials (RCTs) of CPAP versus controls with ≥4 weeks treatment and reported pre- and post-intervention lipid profiles were included. Weighted mean difference (WMD) was used to assess the effect size. Meta-regression was used to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In our study, we observed significant improvements in HDL and triglycerides. Nadeem et al, Shehab et al, Pazarli et al, and Asgari et al, similar to our study, observed that post-CPAP therapy decreases triglycerides and total cholesterol with an increase in HDL; however, on the contrary, Xu et al and Chen et al suggested no clinically significant effect on lipid metabolism [ 29 - 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we observed significant improvements in HDL and triglycerides. Nadeem et al, Shehab et al, Pazarli et al, and Asgari et al, similar to our study, observed that post-CPAP therapy decreases triglycerides and total cholesterol with an increase in HDL; however, on the contrary, Xu et al and Chen et al suggested no clinically significant effect on lipid metabolism [ 29 - 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, moderate-to-severe OSA, daytime sleepiness, CPAP treatment with short-term duration and good compliance were associated with the changes in lipid profile [ 339 ]. In a recent paper by Chen et al, 14 studies with 1792 subjects were included [ 340 ]. The therapy duration was 4-48 weeks.…”
Section: The Effect Of Osa Therapy On the Lipid Metabolismmentioning
confidence: 99%
“…The CPAP therapy significantly decreased the TC levels (−0.09 mmol/L); however, it failed to change the levels of TG (0.07 mmol/L), LDL-C (−0.06 mmol/L) or HDL-C (−0.03 mmol/L). The authors did not find any confounders of CPAP treatment effect on lipid profile changes [ 340 ].…”
Section: The Effect Of Osa Therapy On the Lipid Metabolismmentioning
confidence: 99%
“…However, there are also some reports which present the opposite view, that the concentration of neutrophils does not differ in patients with OSA compared to the healthy population [36,37]. Interestingly, the increased level of neutrophils has also been found in the sputum of patients with OSA, which confirms the existence of a general increased inflammation state among these patients, including their bronchial tree [38].…”
Section: Discussionmentioning
confidence: 80%